Cognition and emotion: a plea for theory. Issue 1 (2nd January 2019) - Reisenzein, Rainer
ABSTRACT: Research on cognition and emotion during the past 30 years has made reasonable progress in theory, methods and empirical research. New theories of the cognition–emotion relation have been proposed, emotion research has become more interdisciplinary, and improved methods of emotion measurement have been developed. On the empirical side, the main achievement of the past 30 years is seen to consist in the reduction of the set of serious contenders for a theory of emotions. Still, several important issues are not fully resolved, including the computational implementation of appraisal processes, the nature of emotions, and the link between emotions and actions. Also, quantitative theories of the cognition–emotion relation need to be refined and tested, and improved theories of the link between emotions and bodily and facial expressions need to be developed. To counter the dangers of theoretical fragmentation and knowledge loss, more efforts should be devoted to the analysis, reconstruction, comparison and integration of important theories and hypotheses in the field of emotion, as well as to the systematization of arguments in favor and against these theories and hypotheses.